Murine macrophage TLR2-FcγR synergy via FcγR licensing of IL-6 cytokine mRNA ribosome binding and translation - Hunt, Danielle (PLoS One, 2018)
Macrophages (MØs) are sentinels of the immune system that use pattern recognition receptors such as Toll-like receptors (TLR) to detect invading pathogens and immune receptors such as FcγR to sense the host’s immune state. Crosstalk between these two signaling pathways allows the MØ to tailor the cell’s overall response to prevailing conditions. However, the molecular mechanisms underlying TLR-FcγR crosstalk are only partially understood. Therefore, we employed an immunologically-relevant MØ stimulus, an inactivated gram-negative bacterium that bears TLR2 agonists but no TLR4 agonist (iB(TLR2)) opsonized with a monoclonal antibody (mAb-iB(TLR2)), as a tool to study FcγR regulation of TLR2-driven production of IL-6, a key inflammatory cytokine. We chose this particular agonist as an investigational tool because MØ production of any detectable IL-6 in response to mAb-iB(TLR2) requires both TLR2 and FcγR signaling, making it an excellent system for the study of receptor synergy. Using genetic, pharmacological and immunological approaches, we demonstrate that the murine MØ IL-6 response to mAb-iB(TLR2) requires activation of both the TLR/NF-κB and FcγR/ITAM signaling pathways. mAb-iB(TLR2) engagement of TLR2 drives NF-κB activation and up-regulation of IL-6 mRNA but fails to result in IL-6 cytokine production/release. Here, Src family kinase-driven FcγR ITAM signaling is necessary to enable IL-6 mRNA incorporation into polysomes and translation. These results reveal a novel mechanism by which FcγR ITAM signaling synergizes with TLR signaling, by “licensing” cytokine mRNA ribosome binding/translation to drive a strong murine MØ cytokine response.